Relational Leadership and Strategic Sustainability in the Management of Tahfidz Programmes: A Case Study at a Madrasah Ibtidaiyah - Siti Khofsah; Zackyl Musthofa; Hefny Hefny (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
The tahfidz program in madrassas not only requires effective memorization learning methods, but also institutional governance that is able to maintain the sustainability of the program. This study aims to analyze the role of relational leadership in building strategic sustainability in the management of tahfidz programs in madrasah ibtidaiyah. The research uses a qualitative approach with a case study design. The informants were selected purposively, consisting of one madrasah head, two tahfidz teachers, and five students. Data were collected through semi-structured interviews, non-participatory observations, and documentation studies, then analyzed through data condensation, data presentation, and conclusion drawing and verification. The validity of the data is strengthened through source triangulation, technical triangulation, and member check. The results of the study show three main findings, namely dialogical communication and professional trust, role collaboration and humanist mentoring, and adaptive monitoring, documentation, and evaluation. The sustainability of the program is built through open working relationships, clear division of responsibilities, mentoring according to the needs of students, and a structured evaluation system. The tahfidz program needs to be managed as part of the institutional system so that it runs consistently, collaboratively, and sustainably.